Fuzzy logic: a contemporary technique in refining physicians’ prescribed total daily insulin dosage for type 2 diabetes patients - Tareq, Md. Tariqul Islam (BRAC University, 2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.